2016
DOI: 10.1097/aln.0000000000000984
|View full text |Cite
|
Sign up to set email alerts
|

G-protein–gated Inwardly Rectifying Potassium Channels Modulate Respiratory Depression by Opioids

Abstract: Background Drugs acting on μ-opioid receptors (MORs) are widely used as analgesics but present side effects including life-threatening respiratory depression. MORs are G-protein–coupled receptors inhibiting neuronal activity through calcium channels, adenylyl cyclase, and/or G-protein–gated inwardly rectifying potassium (GIRK) channels. The pathways underlying MOR-dependent inhibition of rhythmic breathing are unknown. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
104
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 36 publications
8
104
1
Order By: Relevance
“…To further test this concept we manipulated GIRK channels in the preBötC region of adult rats and measured the subsequent changes in respiratory activity. Our results showed that GIRK channel activation at the preBötC decreased rhythmic breathing, a result that was previously identified17. Importantly, we further identified that GIRK channels decreased genioglossus muscle activity.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…To further test this concept we manipulated GIRK channels in the preBötC region of adult rats and measured the subsequent changes in respiratory activity. Our results showed that GIRK channel activation at the preBötC decreased rhythmic breathing, a result that was previously identified17. Importantly, we further identified that GIRK channels decreased genioglossus muscle activity.…”
Section: Discussionsupporting
confidence: 87%
“…NK-1R-expressing preBötC neurons are selectively inhibited by MOR in vitro 14 and respiratory inhibition by MOR depends on GIRK channels17. Since NK-1R excitation inhibits GIRK channels in the nucleus basalis18, excitation of preBötC neurons by NK-1R may also involve GIRK channels.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations